The impact of the number of occult metastatic lymph nodes on postoperative relapse of resectable esophageal cancer. Issue 1 (8th March 2013) - Morimoto, J.; Tanaka, H.; Ohira, M.; Kubo, N.; Muguruma, K.; Sakurai, K.; Yamashita, Y.; Maeda, K.; Sawada, T.; Hirakawa, K.
Summary Clinical stage II/III esophageal cancer (EC), as defined by the Japanese Classification, relapses at a moderately high rate even after curative resection. The number of lymph node metastases is known to be associated with tumor relapse. Recently, the prognostic significance of occult metastatic lymph nodes (MLNs), as well as that of overt MLNs, has been reported. The aim of this study was to investigate the impact of the total number of MLNs including occult MLNs on postoperative relapse in clinical stage II/III EC. One hundred and five patients with clinical stage II/III EC who underwent esophagectomy accompanied by radical lymphadenectomy at the Department of Surgical Oncology in Osaka City University Hospital between January 2000 and October 2008 were included in this study. Occult MLNs, metastases not detected by hematoxylin‐eosin staining, were identified by immunohistochemistry (IHC) using antipancytokeratin antibody AE1/AE3. The clinicopathological features of occult MLNs were compared between the relapse and no relapse groups. A total of 6558 lymph nodes (1357 from two‐field dissection and 5201 from three‐field dissection) were examined by IHC staining; 362 overt MLNs and 143 occult MLNs were detected. The number of occult MLNs increased in proportion to the International Union Against Cancer pathological (p)N‐status and pStage. When the number of occult MLNs was added to the number of pNs, the number of total MLNs was associated with postoperative relapse. With respect to tumor, node, metastasis stage, 6 of 22 patients (27%) who were pathological node‐negative converted to node‐positive by considering total MLNs. The number of N3 patients with relapse increased markedly with restaging by total MLNs. The number of total MLNs, but not overt MLNs, was an independent prognostic factor on multivariate analysis. These results suggest that occult MLNs were often found, and they were associated with postoperative relapse of resectable esophageal cancer. The total number of MLNs including occult MLNs could contribute to evaluating the precise stage of patients with esophageal cancer.